Obce inwestycje bezpośrednie w krajach rozwijających się - Pacyga, Czesław (Wydział Prawa i Administracji UAM, 1975)
The present article deals with direct investments in the developing countries. In part I dynamics, volume and structure of foreign investments are discussed. A decisive importance of direct investments in foreign resources flowing from private sources to the developing countries is stressed. The author pointed to the unequal geographical structure of investments made in the developing countries in the past decade as well as big disproportions in aggregated magnitudes. Particularly characteristic is an important change in the branch structure of direct investments in the underdeveloped countries. While immediately after the Second World War and even in the early sixties the majority of investments was done in the mining sector, at present the greater part of investments is directed to the manufacturing industry. The causes which explain that evolution have also been discussed. In the second part of article the author discussed economic effects of those investments to the underdeveloped countries. Particular attention was devoted to the question to what extent direct investments fill the accumulation gap and to their effects in the sphere of employment. The impact of the inflow of investments upon the balances of payments has been discussed rather extensively and cases were analysed when those investments produced negative effects which contributed to the deficit of payments. In the concluding part of the article the author discussed the possibilities of increasing the role of foreign direct investments in the development of the underdeveloped countries and pointed out that — among other factors — the policy of the governments concerned has a very great importance.
Direct Investments in the Developing Countries